Abraham Miguel Cardoso's Messianism A Reappraisal - Rosenstock, Bruce (1998)
Abraham Miguel Cardoso was born to a crypto-Jewish family living in Rio Seco, Spain, in the year 1626. He left Spain with with his older brother Isaac in 1648. Abraham Cardoso has usually been discussed within the larger context of the Sabbatian movement, which he served as one of its major theoreticians. Until his death in 1706, Cardoso found himself almost constantly under attack by the rabbinical authorities in the cities where he tried to settle with his family, although he sometimes found local non-Jewish authorities who would offer him protection. He served for some time as the personal physician to the bey of Tripoli and later to the local potentate in Tunis. In the last decades of his life, after the death of Sabbatai Zebi, he engaged in bitter debates with other leading Sabbatians about the divinity of the Messiah. Cardoso rejected wholeheartedly what he saw as their adoption of a Christian messialogy. Gershom Scholem's analysis of Cardoso's theology as Gnostic has remained fundamentally unchallenged. Scholem saw in Cardoso's thinking the crystallization of what he believed was the latent antinomian Gnosticism within Kabbalah and especially within the later strata of the Zohar, and he pointed to Cardoso's likely acquaintance with Gnostic ideas, filtered through the Church Fathers (read during theological studies in Spain), as the most significant factor in precipitating this crystallization (see expecially Scholem 1980, pp. 333-334; Scholem 1971a, pp. 65-74; Scholem 1971c, pp. 104-107).